Influence of Irrigating Solutions on Push-Out Bond Strenght of Intraradicular Posts to Dentine - Kaif DDS, Mohammad (2016)
The aim of this study was to evaluate the influence of irrigating solutions commonly used during endodontic treatment on the push-out bond strength of intrarradicular fiber posts to dentin. Thirty single rooted teeth were divided into 3 groups according to the solution used during instrumentation: G1, NaOCL 5.25%; G2, 2% chlorhexidine; G3, distilled water. The root canals were prepared and obturated, and the glass fiber posts were cemented with RelyX ARC®. The specimens were submitted to push-out bond test and the results were analyzed by using the One-way ANOVA. The failure mode data were analyzed using the Chi-square test (P < 0.05). There were no statistically significant differences regarding the irrigant solution factor (P > 0.50). The most predominant failure mode was between posts and resin cement. It was concluded that the different irrigant solutions commonly used in endodontic treatment did not affect the push-out bond strength of fiber posts cemented with resin cement.